Successful laparoscopy-assisted repair of a rectovaginal fistula after low anterior resection for rectal cancer: a report of two cases - Hiroyuki Ohta; Kyozo Hashimoto; Tomoyuki Mizukuro; Byonggu An; Yumi Zen; Yusuke Nishina; Yoshitaka Terada; Naomi Kitamura; Hiroya Akabori; Mitsuhiro Fujino; Eiji Mekata (Surgical Case Reports)
Abstract Background Rectovaginal fistula (RVF) after low anterior resection for rectal cancer is troublesome and refractory. Although various surgical procedures have been previously described, no definitive procedure has shown a satisfactory outcome. We present two consecutive Japanese patients who underwent successful surgery for an RVF after low anterior resection. Case presentation The patients were two women (61-year-old and a 64-year-old). They were admitted to our hospital with a chief complaint of fecal discharge from the vagina after low anterior resection using the double-stapling technique for rectal cancer. They were diagnosed with RVF. Local surgical procedures, including diverting ileostomy, were unsuccessful in previous hospitals. Therefore, we performed laparoscopy-assisted repair of the RVF. In both patients, laparoscopically robust pelvic adhesions were dissected, and the sigmoid colon was transected at just oral side to the RVF. Thereafter, in combination with a perineal approach, the rectum, along with a previous anastomosis and fistula, were completely removed. Surgeries were completed after vaginal repair, redo coloanal anastomosis, and interposition of the dissected connective tissue. In both patients, the postoperative courses were uneventful. They complained of neither recurrence of any RVF nor fecal incontinence 1 year and 10 months after diverting stoma closure. Conclusions A laparoscopy-assisted procedure with reanastomosis and interposition of the perineal connective tissue can be an effective treatment for RVF after low anterior resection for rectal cancer.